Chiến lược ứng phó rủi ro tác động đến thu nhập của nông hộ vùng Tây sông Hậu - Nguyễn Tuấn Kiệt; Trịnh Công Đức; Lê Huỳnh Anh Thư (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
The paper aims to examine the impact of risk and risk response strategies on farmers' income in Western Hau River Zone. The results obtained from 225 surveyed farmers reveal that the farmers were facing three types of risk, namely, weather, pest, and economic risk. In particular, 1.3% of the respondents faced weather risk; 7.1% of farmers faced pest risk; 14.2% of farmers confronted economic risk; 6.2% of farmers faced both weather and pest risk; 10.2% of farmers faced weather and economic risk; and the largest proportion (29.8%) of farmers faced all three types of risk. In order to respond to the aforementioned risks, farmers rendered different strategies in accord with different types of risks such as water management, reduction of investment and farming area, the use of chemicals, finance, extra labor, and self-learning. The regression results show that while risks have a negative and significant impact, response to risk strategies has a positive and significant impact on farmers' income.
Keywords: Rice-shrimp; Risk response; Risk; Western Hau river zone